2008
DOI: 10.1177/0363546508323252
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Intervertebral Disk Degeneration in Athletes

Abstract: Continuous competitive baseball and swimming activities during youth may be associated with disk degeneration. Furthermore, the study indicates that the experience of severe low back pain might be a predictor of disk degeneration in youth. The authors hope that preventive measures and management to protect against disk degeneration and low back pain in athletes will be established by further studies based on these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
170
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 152 publications
(183 citation statements)
references
References 25 publications
5
170
4
2
Order By: Relevance
“…The prevalence of disc degeneration among collegiate rowers was higher than that among coeval nonathletes 5,12) . In collegiate non-athletes (male and female), 31.4% of them had lumbar disc degeneration at 1 or more disc levels 5) .…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…The prevalence of disc degeneration among collegiate rowers was higher than that among coeval nonathletes 5,12) . In collegiate non-athletes (male and female), 31.4% of them had lumbar disc degeneration at 1 or more disc levels 5) .…”
Section: Discussionmentioning
confidence: 73%
“…In previous studies, the relationship between competitive sports activities and disc degeneration has been reported. Disc degeneration was significantly more common in collegiate baseball players and swimmers than in the control group 5) . Moreover, Sward et al 9) reported that the prevalence of disc degeneration in elite gymnasts was significantly higher than that in non-athletes.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations